PENERAPAN KONSELING RATIONAL EMOTIF THERAPY DALAM MENGATASI RASA KURANG PERCAYA DIRI PADA SISWA KELAS X-9 DI SMA N 1 MEJOBO - Lestari, Cristina Puji; Santoso, Santoso; Sucipto, Sucipto (Jurnal Muria Research Guidance and Counseling (MRGC), 2023)
By having confidence, the individual always has a positive attitude and this positive attitude that makes the individual able to develop a positive assessment of both the environment and other people. The type of research used case study research. The subjects were several students of class X-9 who felt less confident. In the school environment, there were still many students who have problems with lack of confidence. This was evidenced by the fact that it was found at SMA N 1 MEJOBO that in class X-9 several students experienced problems, namely not having confidence in students. This research has been designed in the form of a case study. The subjects named CAAR and CARP students who experienced a lack of confidence at SMA N 1 Mejobo. Data collection techniques include interviews, observation, and documentation techniques while data analysis used qualitative data.